Pengaruh Model Pembelajaran Make a Match terhadap Hasil Belajar IPS - Annisaa’ Fitri Aprillia; Indah Wahyu Puji Utami; Joko Sayoni; Aditya Nugroho Widiadi (SAP (Susunan Artikel Pendidikan), 2026)
the National Movement Organization Social Studies material for eighth-grade students of SMPN 1 Turi Lamongan. The main problem in this study is the low motivation and cognitive understanding of students who tend to consider history as boring memorization material. The research method used is quantitative with a quasi-experimental design. Sampling then selected a research sample consisting of 60 students divided into class VIII G as the experimental group and VIII H as the control group. The data collection technique used a validated multiple-choice test instrument. Data analysis was carried out using paired sample t-test and N-gain score test. The results showed that the application of the Make a Match model had a significant effect on learning outcomes, evidenced by the average N-gain score of the experimental class of 78.53% (effective) which far exceeded the control class of 44.14% (less effective). The conclusion of this study is that the use of the Make a Match model significantly influences the mastery of historical concepts through interactive and dynamic learning activities.